Driver Genes Associated With the Incidence of Venous Thromboembolism in Patients With Non-Small-Cell Lung Cancer: A Systematic Review and Meta-Analysis - Qian, Xiaohan; Fu, Mengjiao; Zheng, Jing; Zhou, Jianya; Zhou, Jianying (Frontiers in Oncology, 2021)
Background: The association between driver genes and the incidence of thromboembolic events (TEs) in patients diagnosed with non-small-cell lung cancer (NSCLC) needs to be quantified to guide clinical management. Methods: We interrogated PubMed, Embase, Web of Science and Cochrane library databases for terms related to venous thromboembolism (VTE) and arterial thromboembolism (ATE) in patients diagnosed with non-small-cell lung cancer harboring driver genes. This search was conducted for studies published between 1 January, 2000 and 31 December, 2020. A random-effects meta-analysis was performed to analyze the pooled incidence and odds ratios of VTE in patients with different driver genes. Results: Of the 2,742 citations identified, a total of 25 studies that included 21,156 patients met eligibility criteria. The overall pooled incidence of VTE in patients with driver genes was 23% (95% CI 18-29). Patients with ROS1 rearrangements had the highest incidence of VTE (37%, 95%CI 23-52). ALK rearrangements were associated with the increased VTE risk (OR=2.08 ,95% CI 1.69-2.55), with the second higher incidence of VTE (27%, 95%CI 20-35). Both groups of patients with EGFR and KRAS mutations did not show a significantly increased risk for VTE (OR=1.33, 95% CI 0.75-2.34; OR=1.31, 95% CI 0.40-4.28). Conclusions: ALK rearrangements were shown to be associated with increased VTE risk in patients diagnosed with non-small lung cancer, while there was no significant relation observed between VTE risk and EGFR or KRAS mutations in lung cancer patients.